Clinical and morphological features uterin corpus cellular leiomyoma - Ye. V. Mischenko; Ye. Ye. Grigoriyeva; A. M. Avdalyan; V. V. Klimachev; T. B. Klimacheva (Бюллетень сибирской медицины, 2010)
Analysis of clinical-anamnestic and morphological features of a cellular and simple leiomyoma of a uterus is leading. Features of a leiomyoma of a uterus with cellular texture of the site are determined: young age, monthly since 15 years ((20,0 ± 4,6)%), often use ВМК ((38,7 ± 5,6)%), an infrequent combination to infringement of genesial function. Analysis of СD31, Ki-67, and Ag-NORproteins expression in the greater and smaller tumour which have been taken away from one macropreparation was carried out.